Effect of Freeze-Thaw Cycles on the Mechanical Properties of Polyacrylamide- and Lignocellulose-Stabilized Clay in Tibet. (28th September 2021) - Shi, Haiping; Li, Zhongyao; Li, Wenwei; Wang, Shaopeng; Wang, Baotian; Wang, Peiqing
Abstract : Laboratory freezing experiments were conducted to evaluate the effect of polyacrylamide (PAM) and lignocellulose on the mechanical properties and microstructural characteristics of Tibetan clay. Direct shear and unconfined compressive tests and field emission scanning electron microscopy analyses were performed on clay samples with different contents of stabilizers. The test results show that the addition of PAM can improve the unconfined compressive strength and cohesion of Tibetan clay, but an excessive amount of PAM reduces the internal friction angle. After several freeze-thaw cycles, the unconfined compressive strength and cohesion of samples stabilized by PAM decrease significantly, while the internal friction angle increases. Samples stabilized by PAM and lignocellulose have higher internal friction angles, cohesion, and unconfined compressive strength and can retain about 80% of the original strength after 10 freeze-thaw cycles. PAM fills the pores between soil particles and provides adhesion. The addition of lignocellulose can form a network, restrict the expansion of pores caused by freeze-thaw cycles, and improve the integrity of PAM colloids. It is postulated that the addition of a composite stabilizer with a PAM content of 0.4% and a lignocellulose content of 2% may be a technically feasible method to increase the strength of Tibetan clay.